ANALISIS PENGARUH DIFERENSIASI PRODUK TERHADAP KEPUASAN KONSUMEN PADA TOKO MOTOR JAYA SIDOARJO - Bayu Wega Parahita; Mohammad Ramadhani; Nindya Kartika Kusmayati (PUTRA JAWA PUBLISHER, 2024)
The changes that occur in the business world today are truly uncertain. For this reason, every company that wants to win the competition and be successful in this century must apply the concept of product differentiation so that the company can use all existing resources and advantages in taking advantage of all changes to win the competition. This differentiation is very important and suitable as the key to success in a company, so this research was conducted with the aim of finding out the effect of product differentiation on customer satisfaction at the Jaya Sidoarjo Motor Shop. In running its business, companies must implement differentiation, where differentiation is one type of competitive advantage that a company can have. Because it is suspected that the application of product differentiation has a great influence on consumer satisfaction in a company. This research was carried out by conducting research on the product differentiation policy at the Jaya Motor Shop Sidoarjo. The method used is simple regression method and correlation coefficient and t test to see the influence and relationship of product differentiation on customer satisfaction. The research results show that product differentiation has a strong relationship with consumer satisfaction at the Jaya Sidoarjo Motor Shop. It can be concluded that key to the success of Toko Motor Jaya Sidoarjo in reaching and serving the market must be implementing the concept of product differentiation which can increase customer satisfaction and continue to be a successful company and be able to win the competition.